2021
DOI: 10.1371/journal.pone.0247510
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of ACE2 protein expression in rodent, non-human primate, and human respiratory tract at baseline and after injury: A conundrum for COVID-19 pathogenesis

Abstract: Angiotensin converting enzyme 2 (ACE2) is the putative functional receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Current literature on the abundance and distribution of ACE2 protein in the human respiratory tract is controversial. We examined the effect of age and lung injury on ACE2 protein expression in rodent and non-human primate (NHP) models. We also examined ACE2 expression in human tissues with and without coronavirus disease 19 (COVID-19). ACE2 expression was detected at ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…It has been indicated that neuropilin 1 (NRP1) has a role in potentiating SARS-CoV-2 entry through the ACE2 pathway (6,7). Studies from other coronaviruses provided evidence for CD147 and the 78-kDa glucose-regulated protein (GRP78) as putative alternative receptors, but more investigations on how the collective tissue distribution of these factors correlate with viral tropism and disease symptoms are under active investigation (8,9).…”
Section: Viral Entry and Tropismmentioning
confidence: 99%
“…It has been indicated that neuropilin 1 (NRP1) has a role in potentiating SARS-CoV-2 entry through the ACE2 pathway (6,7). Studies from other coronaviruses provided evidence for CD147 and the 78-kDa glucose-regulated protein (GRP78) as putative alternative receptors, but more investigations on how the collective tissue distribution of these factors correlate with viral tropism and disease symptoms are under active investigation (8,9).…”
Section: Viral Entry and Tropismmentioning
confidence: 99%
“…This observation can account for the reduced fusion activity when compared with other variants under the same conditions. It can also explain why Omicron replicates better in the upper respiratory tract than lung as the former has much higher levels of ACE2 (51,52). The transition from the closed to the RBD-up conformation in an S trimer typically requires an order-disorder transition in the FPPR and 630 loop.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 enters host cells, such as respiratory epithelial cells, by binding to ACE2, which is a type I transmembrane glycoprotein with carboxypeptidase activity; however, the abundance and distribution of ACE2 in human lungs are elusive. For instance, ACE2 is expressed at high levels in alveolar type II cells (AT2s) ( 20 ), which are rare ciliated epithelial and endothelial cells present in the trachea, but not in the lungs ( 21 ). In other studies, AT2 as well as ciliated cells in human lungs were shown to express ACE2 ( 22 ).…”
Section: Discussionmentioning
confidence: 99%